MENCERMATI BENTUK INFLEKSI DAN DERIVASI DALAM BAHASA INDONESIA - Diana Tustiantina (Universitas Sultan Ageng Tirtayasa, 2016)
The concept of derivation and inflection in general discusses the morphological processes that cause a wide variety of formations. Both of these formations can be the same word class status of the basic word or words from the class change basically. Talking about the derivation and inflection cannot be separated from the concept of the word class. One distinguishing feature of these two processes is the class status of said formation resulting from the process of dasarnya.Perbedaan fundamental form of two terms it is the presence or absence of the word class change. The derivation is a process that involves changing morphological classes of words from its basic form. Instead, inflection does not result in said class. Derivation and inflection term used to describe the process by showing morphological change in shape with the state of the category, namely a change in category or not. The essence of both of these processes is characterized by a state of word class or category in the formation resulting from the process morfologis.Kelas Indonesian word much discussed by language experts, one of whom Harimurti Kridalaksana (1986), which classifies the division said as many as 13 classes of words. The division includes verbs, adjectives, nouns, pronouns, numeralia, adverbs, interogativa, demonstrativa, article, prepositions, conjunctions, Phatic category, and interjections. Based on the above background, the authors are interested membahasderivasi and inflection dalambahasa Indonesia. This process in the Indonesian language has its own peculiarities in reflecting the derivation and inflection.